Canadians Who Care: Social Networks and Informal Caregiving Among Lesbian, Gay, and Bisexual Older Adults in the Canadian Longitudinal Study on Aging. (October 2020) - Ismail, Mariam; Hammond, Nicole G.; Wilson, Kimberley; Stinchcombe, Arne
Canada is experiencing population aging and evidence on the provision of care is based on data collected from majority populations. This analysis compared social networks and patterns of care provision between heterosexual and lesbian, gay, and bisexual (LGB) Canadians between the age of 45 and 85 years. Data were drawn from the Canadian Longitudinal Study on Aging (CLSA), a large national study of health and aging. The results from analysis of baseline data showed that LGB participants were less likely to have children and reported seeing their friends more recently than heterosexual participants. Gay and bisexual men were more likely to provide care support in comparison to heterosexual men. LGB participants were more likely to provide care to friends. The results highlight the importance of considering distinct social networks in the development of policy and practice approaches to support a diverse aging population.